A Blended Laboratory-Based Learning Model for Embedded Systems Education - Inchan, Surasak; Akatimagool, Somsak (Journal of Technical Education and Training, 2025)
This research aims to develop a blended learning model tailored for laboratory instruction in embedded systems education. The proposed model is designed to replace traditional instructional methods, which often lack opportunities for reflection and fail to motivate learners sufficiently. Initially, the research identified existing challenges in teaching and learning practices and the core competencies required of undergraduates for the embedded systems. Subsequently, a blended laboratory-based learning model was designed to enhance students’ practical skills in alignment with Industry 4.0 demands. Classroom action research was employed as the framework for developing the PPED model, encompassing four steps: planning, practice, assessment, and discussion. The instructional package included a teacher’s manual, an experimental kit, simulation software, worksheets, and assessment tests. The study sample comprised undergraduate students enrolled in the Digital Circuit Design course within the Department of Information and Communication Engineering, at the Faculty of Engineering and Industrial Technology, Phetchaburi Rajabhat University. Findings indicated that the quality of the instructional package was rated as highly appropriate by both experts and students. Furthermore, the PPED model’s quality was assessed as highly relevant for laboratory learning. The PPED model’s efficiency met the established standard criteria based on process and outcome performance evaluation, passing the E1/E2 standard with scores of 74.38% and 72.29%, respectively. Additionally, student satisfaction with the instructional package was rated as very high. This research highlights the integration of diverse teaching methods and innovative instructional media, emphasizing active learning engagement in the educational process. The PPED model supports knowledge and experience construction through hands-on activities, fostering behavioral change, enriching students’ learning experiences, and promoting lifelong learning skills. In conclusion, the study underscores the importance of modernizing instructional approaches by integrating educational technology and diverse pedagogical methods within a conducive classroom environment. Such a blended laboratory-based learning approach is crucial for advancing educational practices to meet the demands of 21st-century learners in an ever-evolving learning world.